Primary breast lymphoma of childhood: a case report and review of literature - Giulia A. Restivo; Marta Pillon; Lara Mussolin; Clara Mosa; Angela Guarina; Angela Trizzino; Salvatore Ialuna; Elisa Carraro; Emanuele S.G. D'Amore; Giovanna Russo; Caterina Elia; Maurizio Mascarin; et al. (BMC, 2021)
Abstract Background Primary breast lymphoma (PBL) is an extremely rare neoplasm in children; by definition, it manifests in the breast without evidence of lymphoma elsewhere, except ipsilateral axillary nodes. Case presentation We report a case of a 15-year-old girl diagnosed with diffuse large B-cell lymphoma (DLBCL) of the right breast: the patient received chemotherapy and rituximab, achieving complete remission. A literature review revealed other 11 cases of pediatric PBL; it mainly affects female adolescents and can involve right and left breast equally. Different histologic subtypes have been described, arising from both B-cell and T-cell. Therapeutic approaches were very different, from chemotherapy to local treatment with surgery and/or radiotherapy. Conclusions Our case is the first in which rituximab was administered, suggesting to be a promising therapy in B-cell PBL, as already demonstrated in pediatric B-cell lymphoma from other sites. Further investigations are needed to identify prognostic factors and establish the most effective treatment.